2004
DOI: 10.1126/science.1097576
|View full text |Cite
|
Sign up to set email alerts
|

Toward Heisenberg-Limited Spectroscopy with Multiparticle Entangled States

Abstract: The precision in spectroscopy of any quantum system is fundamentally limited by the Heisenberg uncertainty relation for energy and time. For N systems, this limit requires that they be in a quantum-mechanically entangled state. We describe a scalable method of spectroscopy that can potentially take full advantage of entanglement to reach the Heisenberg limit and has the practical advantage that the spectroscopic information is transferred to states with optimal protection against readout noise. We demonstrate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
628
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 622 publications
(635 citation statements)
references
References 24 publications
5
628
0
2
Order By: Relevance
“…It means that for SSS, its fluctuation of the collective angular momentum is squeezed in one direction and inflated in the another direction, and the fluctuation in the squeezed direction is smaller than the sub-short limit. It is believed that spin squeezing which is aroused from quantum correlation effect among individual particles, is closely related to multipartite entanglement [9,11,16,41]. One of the main applications of the SSSs is used to reduce quantum noise and increase the signal-to-noise ratio in spectroscopy [10,11,42,43].…”
Section: Spin Squeezingmentioning
confidence: 99%
See 1 more Smart Citation
“…It means that for SSS, its fluctuation of the collective angular momentum is squeezed in one direction and inflated in the another direction, and the fluctuation in the squeezed direction is smaller than the sub-short limit. It is believed that spin squeezing which is aroused from quantum correlation effect among individual particles, is closely related to multipartite entanglement [9,11,16,41]. One of the main applications of the SSSs is used to reduce quantum noise and increase the signal-to-noise ratio in spectroscopy [10,11,42,43].…”
Section: Spin Squeezingmentioning
confidence: 99%
“…Equation (1) shows that a quantum state with the APEP-enhancing must be entangled. Besides entangled states, it has been theoretically and experimentally demonstrated that spin squeezed states (SSSs) can also be used to improve the accuracy of estimation [8,9,10,11,12,13,14,15,16,17,18,19]. The concept of SSSs was first established by Kitagawa and Ueda [9].…”
Section: Introductionmentioning
confidence: 99%
“…In the atomic literature, where |a and |b refer to different atomic levels, |ψ (N) 0 often is referred to as "spin-squeezed state" [42,43] or "Schrödinger-cat state" [44][45][46]. It has been experimentally demonstrated using trapped ions [44][45][46][47], Bose-Einstein condensates [48], macroscopic atomic ensembles [49], and NMR [50]. 5 The map Φx is called programmable if one can express it in terms of a constant interaction with an external ancillary system B whose initial state encodes the dependence on the parameter x, i.e.…”
Section: Quantum Parameter Estimation For Channelsmentioning
confidence: 99%
“…Starting with two-qubit gate operations [2,3], long lived two-qubit entanglement [4,5,6], teleportation experiments [7,8], and different sorts of multi-qubit entangled states [9,10,4,11], the record for qubit-entanglement is currently presented in a 6-qubit cat state and a 8-qubit W-state [12,13]. Future improvement is expected using the technique of segmented linear Paul traps which allow to shuttle ions from a "processor" unit to a "memory" section [14].…”
Section: Introductionmentioning
confidence: 99%